Architectural Development of Lusi Island Tourism and Natural Conservation Area in Sidoarjo Regency - Mulkan, Muhammad Balya Ibnu; Sadana, Agus S (Institut Seni Indonesia Denpasar, 2024)
Lusi Island was formed from Sidoarjo mud in Sidoarjo, East Java, Indonesia. This artificial island can be developed into a mud-based tourism area that represents natural events and conservation in mangrove forests. Based on regional architectural principles, this research is aimed at developing and designing educational tourism areas including creating tourist zoning, facilities and supports including educational tourism. The process of designing the Lusi Island Tourism and Nature Conservation Area was carried out by combining data from field surveys, literature studies and precedent studies. The research results show that the tourism area created includes mangrove planting activities including witnessing the Lapindo mud remains which is supported by adventure tourism, such as off-roading, camping and outbound. The facility space program includes accommodation, prayer room, toilets, culinary center, and supporting space consisting of waste water management installations. The benefits of developing Lusi Island as a tourism and nature conservation area that applies the principles of building environmentally friendly and sustainable areas as well as tropical architectural buildings to become the main attraction for tourists.